2015
DOI: 10.11648/j.jfns.20150303.16
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Phytochemical Profile of Niger Cultivated Date Palm (Phoenix Dactilyfera L)

Abstract: Abstract:The chemical constituents available in plants have been reported to vary with the geographical location of the plants. This investigation assessed the nutritional and phytochemical profile of Niger date palm (Khaokhara) fruit and sought to determine any uniqueness of Niger cultivate Date palm relative to Date palms cultivated in other regions. Standard procedures as described by AOAC were employed in the analyses. The moisture, crude protein and fat contents were determined to be 13.40, 2.67 and 0.70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…The highest value for potassium was recorded with Maktoomi. Contrary to the ndings of the present study, Abdrabo et al [30] reported a higher concentration of potassium that ranged from 3500 mg/kg to 7500 mg/kg (Abdrabo, 2015). The sodium concentration of date samples was in the range of 7.46 mg/100g to 14.47 mg/100g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The highest value for potassium was recorded with Maktoomi. Contrary to the ndings of the present study, Abdrabo et al [30] reported a higher concentration of potassium that ranged from 3500 mg/kg to 7500 mg/kg (Abdrabo, 2015). The sodium concentration of date samples was in the range of 7.46 mg/100g to 14.47 mg/100g.…”
Section: Discussioncontrasting
confidence: 99%
“…Sultana reported high carbohydrate content while Lulu and Shebeby recorded low carbohydrates of 70.22 g/100g and 70.64 g/100g, respectively. Oni and Sadiq et al reported a similar carbohydrate content in Nigerian PDF (Oni, 2015;Sadiq, 2013).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Date fruits have a high nutritional being rich in carbohydrates, proteins, minerals, vitamin B complex such as thiamine (B1), riboflavin (B2), niacin (B3), pantothenic (B5), pyridoxine (B6), folate (B9) (Al-Harrasi et al, 2014). Phytochemically date palm contains alkaloids, flavonoids, anthraquinone, saponin, terpenoids and tannin (Oni et al, 2015). Escherichia coli and Bacillus cereus are pathogenic bacteria that cause infection foodborne with diarrhea symptoms.…”
Section: Introductionmentioning
confidence: 99%